Study on prevalence of ESBL producing multi drug resistant E. coli in livestock and poultry in Patna district of Bihar state, India - ARCHANA; PURUSHOTTAM KAUSHIK; ANJAY; BHOOMIKA; SEULI SAHA ROY; BABLU KUMAR; ANIL KUMAR; MANOJ KUMAR; SAVITA KUMARI; SAURABH SWAMI (Indian Journal of Animal Sciences)
Antimicrobial resistance is considered one of the greatest public health threat undermining the effectiveness of antibiotics. Occurrence of Extended spectrum beta-lactamase (ESBL) producing multidrug resistant (MDR) E. coli in human and animal poses a clinical and epidemiological challenge. The aim of the present study was to determine the occurrence of ESBL-producing MDR E. coli among healthy livestock and chicken and to investigate the types of ESBL genes circulating among livestock in Patna district of Bihar. A total of 254 samples from apparently healthy animals and chickens were collected from sixteen villages of Patna district which comprised of raw milk, rectal swabs and chicken cloacal swab. Out of 254 samples processed a total 148 isolates were confirmed as E. coli. After isolation and confirmation of E. Coli resistance profile were generated by disc diffusion method. The antimicrobial resistance profile of isolates revealed that 85.13% isolates were resistant to amoxicillin/ clavulanate; 72.97% to cefpodoxime; 37.83% resistant to ampicillin; 33.10% to ceftazidime; 27.02% to nalidixic acid; 26.35% to cefoxitin; and 23.64% to trimethoprim. However, 97.98% isolates were found susceptible to amikacin and 100% were sensitive to imipenem. The MDR analysis showed that 54.05% of isolates have MAR index ≥0.25 and 8.1% of isolates have MAR index ≥0.5. Further, out of 148 E. coli isolates tested for ESBL production, 30 isolates were found ESBL producer. The study provides data on prevalence of MDR ESBL producing E. coli among livestock in Bihar, India, indicating the risk of transmission of pathogens to humans through horizontal transmission.